Effects of a Web‐Based Patient Decision Aid on Biologic and Small‐Molecule Agents for Rheumatoid Arthritis: Results From a Proof‐of‐Concept Study. Issue 3 (6th February 2018) - Li, Linda C.; Shaw, Chris D.; Lacaille, Diane; Yacyshyn, Elaine; Jones, C. Allyson; Koehn, Cheryl; Hoens, Alison M.; Geldman, Jasmina; Sayre, Eric C.; Macdonald, Graham G.; Leese, Jenny; Bansback, Nick
Abstract : Objective: To assess the extent to which ANSWER‐2, an interactive online patient decision aid, reduces patients' decisional conflict and improves their medication‐related knowledge and self‐management capacity. Methods: We used a pre–post study design. Eligible participants had a diagnosis of rheumatoid arthritis (RA), had been recommended to start using a biologic agent or small‐molecule agent or to switch to a new one, and had internet access. Access to ANSWER‐2 was provided immediately after enrollment. Outcome measures included 1) the Decisional Conflict Scale (DCS), 2) the Medication Education Impact Questionnaire (MeiQ), and 3) the Partners in Health Scale (PIHS). A paired t ‐test was used to assess differences pre‐ and postintervention. Results: The majority of the 50 participants were women (n = 40), and the mean ± SD age of participants was 49.6 ± 12.2 years. The median disease duration was 5 years (25th, 75th percentile: 2, 10 years). The mean ± SD DCS score was 45.9 ± 25.1 preintervention and 25.1 ± 21.8 postintervention (mean change of −21.2 of 100 [95% confidence interval (95% CI) −28.1, −14.4], P < 0.001). Before using ANSWER‐2, 20% of participants had a DCS score of <25, compared to 52% of participants after the intervention. Similar results were observed in the PIHS (mean ± SD 25.3 ± 14.8 preintervention and 20.4 ± 13.0 postintervention; mean change of −3.7 of 88 [95% CI −6.3, −1.0], P = 0.009). Findings from the MeiQ were mixed, with statistically significant differences found only in the self‐management subscales. Conclusion: Patients' decisional conflict decreased and perceived self‐management capacity improved after using ANSWER‐2. Future research comparing the effectiveness of ANSWER‐2 with that of educational material on biologic agents will provide further insight into its value in RA management.